A multicenter investigation of OPTI-FREE(RM) RepleniSH(RM) multi-purpose disinfecting solution impact on soft contact lens patient comfort - Glenn S Corbin (Dove Medical Press, 2010)
Glenn S Corbin1, Linda Bennett2, Louis Espejo3, Suzanne Carducci4, Andrew Sacco5, Robert Hannigan6, Stuart Schatz71Wyomissing Optometric Center, Wyomissing, PA, USA; 2Bellmont, MA, USA; 3Rockville, MD, USA; 4Gaithersburg, MD, USA; 5Vestal, NY, USA; 6Taunton, MA, USA; 7College Park, MD, USAObjective: Demonstrate that successful soft contact lens wearers using competitive multipurpose solutions report improvement in comfort with OPTI-FREE® RepleniSH® Multi-Purpose Disinfecting Solution (MPDS).Methods: This 30-day, multicentered, open-label study enrolled 109 eligible soft contact lens wearers using COMPLETE® Multi-Purpose Solution (MPS) Easy Rub® or ReNu MultiPlus® MPS. The test solution (OPTI-FREE® RepleniSH® MPDS) was dispensed for use in place of habitual care solutions. Subjects assessed their experience with their habitual solution (baseline) and the test solution (Day 30) using Likert-style questions. Contact lens acuity and biomicroscopy findings were recorded at each visit.Results: The test solution was associated with a statistically significant improvement in instillation comfort (P = 0.02), end of day comfort (P < 0.0001), clear vision (P < 0.0001) and overall satisfaction (P < 0.001). Subjects reported the test solution enhanced their overall lens-wearing experience more effectively than their previous solution (P < 0.0001) and that they would continue test solution use after the study (P < 0.0001).Conclusions: The test solution was effective at improving comfort and overall contact lens experience compared to COMPLETE® MPS Easy Rub® or ReNu MultiPlus® MPS in successful contact lens wearers. These results indicate that changing contact lens care solutions, even in successful lens wearers, may improve comfort and overall lens-wearing experience.Keywords: multipurpose solution, soft contact lens, disinfecting solution, patient comfort